APPLYING OF WASHING DISINFECTANT LIQUIDS FOR DISPENSERS FOR DISINFECTION OF LIVESTOCK BUILDINGS - Кушнир, Сергей (SWorldJournal, 2020)
In this article we consider the effectiveness of usage of detergent disinfectant liquid PAOS-SD combined with a foam generator, as well as an assessment of the effectiveness of disinfecting a room in the presence of livestock.